Identification of Green Building Factors in Faculty of Engineering Building and Faculty of Fishery Building of Teuku Umar University - Samsunan, Samsunan; Ikhsan, Muhammad (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
Construction of buildings without considering environmental conditions such as the accuracy of land use, the use of energy (electricity), water and the use of building materials impact on the quality of life around it. This study aims to determine the criteria of green building based on the Greenship-GBCI standard of building code. The object of research on the building Faculty of Engineering and Faculty of Fisheries by way of direct observation and verification interviews. Based on data collected and calculations on 41 Greenship criteria from six categories: Appropriate Site Development (ASD), Energy Efficiency and Conservation (EEC), Water Conservation (WAC), Material Resource and Cycle (MRC), Indoor Health and Comfort (IHC) and Building Environment Management (BEM), Faculty of Engineering building and Faculty of Fisheries building total points of 29 points from 117 maximum points consisting of ASD; EEC; WAC; MRC; IHC and BEM respectively are 9; 1; 0; 6; 10; and 5 points. The highest IHC category value is 10 points, while the lowest category of EEC is 0.Based on the identification results indicate that the building has not met the criteria as a building that was built to apply the concept of Green Building.